STRATEGI PEDAGOGI KREATIF DALAM MENGHADAPI ZERO ATTENTION SPAN PADA SISWA PENGGUNA TIKTOK DAN REELS: KAJIAN LITERATUR TERHADAP PENDEKATAN PEMBELAJARAN ERA DIGITAL - Itsna Rusydiana Itsna (Al-Mudarris: Journal Of Education, 2025)
The rapid evolution of digital technologies has significantly influenced the way students engage with information, particularly with the widespread use of short video applications such as TikTok and Instagram Reels. These platforms, while offering entertainment and easily digestible content, also contribute to the phenomenon of "zero attention span," wherein students' ability to concentrate on lengthy, complex educational tasks diminishes. This literature review explores the pedagogical strategies that can be employed to address the challenges posed by this phenomenon in the context of modern education. By examining the intersection of digital media consumption and learning behaviors, the study identifies the potential benefits and drawbacks of integrating platforms like TikTok and Instagram Reels into educational practices. The research highlights the importance of utilizing interactive and visually appealing elements within educational content to maintain student engagement and foster deeper learning. Moreover, the review stresses the need for educators to develop curricula that are both adaptive to the digital-native learning style and capable of enhancing cognitive focus and critical thinking. Strategies such as gamification, multimedia use, and interactive videos are proposed as effective tools to capture students' attention while ensuring academic rigor. The findings underscore the necessity of balancing entertainment with educational depth in the digital learning environment. Ultimately, this study provides valuable insights for educators seeking to navigate the complexities of modern attention spans and utilize technology in a manner that enhances, rather than detracts from, educational outcomes.